Strategi Guru dalam Mengatasi Tantangan Pembelajaran Tahfidz di Tahfidz Intensive Center - Saidah Nur Beby; Kamil Kamil; Fuji Rahmadi (Medan Resource Center, 2026)
This study aims to evaluate teachers’ strategies in addressing learning challenges in Qur’an memorization (tahfidz) at the Tahfidz Intensive Center (TIC) in Medan. The study focuses on the effectiveness of instructional strategies, their alignment with students’ characteristics, and their impact on memorization outcomes.This research employs a qualitative evaluative approach. Data were collected through observations, semi-structured interviews, and documentation involving active students, tahfidz teachers, and the head of the tahfidz program. Data analysis was conducted through the processes of data reduction, data display, and conclusion drawing, while the validity of the findings was ensured through source and method triangulation. The findings indicate that structured stages of tahfidz, the application of the tikrar (repetition) method, continuous monitoring through a tiered evaluation system, and emotional–spiritual mentoring contribute positively to the quality of students’ memorization. However, challenges persist in maintaining the consistency of revision (muroja’ah) and ensuring long-term retention of memorization. The study concludes that flexible instructional strategies, strengthened discipline, sustained motivational support, and the integration of individualized learning approaches with adaptive pacing are essential to enhancing the effectiveness of tahfidz learning.